Sepedon (Diptera: Sciomyzidae) species from China, with notes on taxonomy and distribution - Li, Zhu; Yang, Ding (Zootaxa, 2017)
All eight species of the genus Sepedon Latreille (Diptera: Sciomyzidae) known from China are reviewed and keyed, with diagnoses, photographs, and discussion. Geographic distributions of all species are updated and discussed, and distribution maps are presented. Sepedon spinipes (Scopoli) is recorded for the first time as occurring in China.